The Value of Fitrah and its Relationship with Islamic Education - MHD Harmidi HRP; Tengku Sarina Aini Binti Tengku Kasim; Ahmad Bin Yussuf (al-Afkar, Journal For Islamic Studies, 2024)
The purpose of this study is to explore further the meaning of fitrah and its relationship with Islamic education. As in many references, the concept of fitrah is an innate natural thing inherent in human beings brought from birth. Fitrah means the potential possessed by humans. The potential will have a positive impact on human development if developed through the process of Islamic education. This study uses a qualitative method of library research. The results of this study indicate that humans are born with different potentials. There is potential for good and there is also potential for bad. This potential will later develop into its power which, if managed properly, will be able to produce civilization through a good educational process. The goal of Islamic education should be to educate to face Islam, meaning that Islamic education is directed so that students are more inclined to the teachings of Islam. At the same time, fitrah also means that Islamic education serves to know the nature of God and at the same time know himself. By using a literature approach, through the review of authoritative books and journals, this paper will try to take a comprehensive look at the discourse of the term fitrah in terms of language, the meaning of the Qur'an and Hadith, fitrah in the view of philosophy and psychology.